Molecular docking study of various Enterovirus—A71 3C protease proteins and their potential inhibitors - Le, Tran Thao Vy; Do, Phuc-Chau (Frontiers in Microbiology, 2022)
Hand, foot, and mouth disease is a common infection that primarily affects children in preschool and kindergarten; however, there is yet no vaccination or therapy available. Despite the fact that current research is only focused on numerous strains of Enterovirus - A71 (EV-A71) 3C protease (3Cpro), these investigations are entirely separate and unrelated. Antiviral agents must therefore be tested on several EV strains/ mutations. Twenty-one previously reported inhibitors were evaluated for inhibitory effects on eight EV-A71 3Cpro, including wild-type and mutant proteins in this study, as well as another twenty-nine powerful candidates with inhibitory effects on EV-A71 were investigated using the molecular docking approach. This method is to determine the broad spectrum of the antiviral agents on a range of strains/mutants because the virus frequently has mutations. Even though Rupintrivir is reported to pass phase I clinical trial, 4-Iminooxazolidin-2-one moiety (FIOMC) was shown to have a broader anti-3Cpro spectrum than Rupintrivir. Meanwhile, Hesperidin possessed a better 3Cpro inhibitory capability than FIOMC. Thus, it could be considered the most promising candidate for inhibiting various strains of EV-A71 3Cpro proteins in the newly anti-EV compounds group. Furthermore, the mutation at E71A has the most significant impact on the docking results of all ligands evaluated. Future in vitro experiments on Hesperidin's ability to inhibit 3Cpro activity should be conducted to compare with FIOMC's in vitro results and validate the current in silico work.